Analisis Strategi Pemasaran Pupuk Organik Guano Bali Organikultur pada PT. Wedhatama Sukses Makmur di Provinsi Bali - VITRIA WULANDARI; KETUT BUDI SUSRUSA; RATNA KOMALA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Marketing Strategy Analysis for Guano Bali Organikultur Organic Fertilizer PT. Wedhatama Sukses Makmur should apply the STP (Segmenting, Targeting, Positioning) strategy if the company is to stay in the organic fertilizer market competition and expand its market internationally.This research was conducted in two places, namely Asta Sari Store and Sanjiwani Orchid Store with 72 respondents selected through accidental sampling. The analysis used in this study include: (1) cluster analysis (2) crosstab analysis and (3) MDS analysis. The result of cluster analysis based on behavioral, psychographic, and consumer demographic variables forms three segments, namely Segment-1, Segment-2, and Segment-3. The right segment to be targeted is Segment-2. Bali Organikultur fertilizer is a market follower and based on the perception map from MDS analysis it is close to POC NASA fertilizer which means that both of them have similarities and a high level of competition. Facing the dynamics of competition, the company needs to maintain product quality, maintain price stability, need to implement a marketing mix strategy, and conduct further studies of the strategies that must be carried out as a market follower.